1994
DOI: 10.1002/ar.1092380306
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, histochemical, and myosin isoform analysis of the diaphragm of adult horses, Equus caballus

Abstract: The horse provides an interesting model for study of the structure and function of the mammalian diaphragm. Multiple regions of diaphragm from seven adult horses were prepared for histochemistry, immunocytochemistry, myosin heavy chain electrophoresis, and native myosin electrophoresis. Two additional adults were dissected to demonstrate myofiber and central tendon morphology and stained for acetylcholinesterase to demonstrate motor endplates. All regions of the adult diaphragm were histochemically characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 30 publications
0
20
1
1
Order By: Relevance
“…Later, electrophoretic methods similar to those used in the present study were applied on samples from equine biceps brachii (Hermanson et al, 1991) and diaphragm (Cobb et al, 19941, but only a single fast MyHC was observed. The difference between these two studies and the present results might be explained by the fact that horse biceps brachii (Hermanson et al, 1991) and diaphragm (Cobb et al, 1994) muscles are exclusively composed of type I and type IIA muscle fibers. Sosnicki et al (1989) identified fast and slow fiber types in horse skeletal muscle by differences in the mobility of their MyHCs.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Later, electrophoretic methods similar to those used in the present study were applied on samples from equine biceps brachii (Hermanson et al, 1991) and diaphragm (Cobb et al, 19941, but only a single fast MyHC was observed. The difference between these two studies and the present results might be explained by the fact that horse biceps brachii (Hermanson et al, 1991) and diaphragm (Cobb et al, 1994) muscles are exclusively composed of type I and type IIA muscle fibers. Sosnicki et al (1989) identified fast and slow fiber types in horse skeletal muscle by differences in the mobility of their MyHCs.…”
Section: Discussioncontrasting
confidence: 99%
“…In a more recent immunocytochemical study using anti-slow (5-4D), anti-fast (lAlO), and anti-fast red (5-2B) MAbs with cross reactivity for type I, all type I1 and type IIa MyHCs, respectively, in a number of species, did not enable subclassification of type I1 MyHCs in equine gluteus medius muscle (Sinha et al, 1992). Similarly, a clear discrimination between fibers containing either slow or fast MyHCs has been obtained by immunohistochemistry in both horse diaphragm (Cobb et al, 1994) and gluteus medius muscle (Serrano et al, 1996), but subdivision of type I1 fibers was not possible. Nevertheless, only MAbs directed against slow and all fast MyHC isoforms were tested in these latter studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To our knowledge, Weddell seals are the first reported example where there is a shift from aerobic Type I fibers towards an increase in Type IIA oxidative fibers with a significant decrease in mitochondrial density as the animals mature. By contrast, the locomotor muscles of precocial terrestrial mammals are similar in mass (as a percentage of total body mass) and fiber type composition across age classes (Cobb et al, 1994a;Cobb et al, 1994b;Dearolf et al, 2000;Schutt et al, 1994).…”
Section: =0mentioning
confidence: 91%
“…These electrophoresis parameters have previously been shown to provide optimal separation and imaging of the bands representing myosin isoforms. 8,32 Western blot An acrylamide gel containing separated protein from the laryngeal muscles of a normal horse was transferred onto a nitrocellulose membrane at 100 mA overnight at 4uC. The membrane was blocked and incubated with a primary monoclonal antibody against all MHC isoforms (mouse anti-human MHC; Developmental Studies Hybridoma Bank, University of Iowa, Iowa City, Iowa) for 1 hour (1 : 1000).…”
Section: Protein Extraction and Sds-pagementioning
confidence: 99%